Cytokine and microbiota profiles in obesity-related hypertension patients - Aguirre-García, María Magdalena; Amedei, Amedeo; Hernández-Ruiz, Paulina; Gómez-García, Ana Pamela; Niccolai, Elena; Moreno-Rodríguez, Aura M.; Pinto-Cardoso, Sandra; Alviter-Plata, Adriana; Escalona-Montaño, Alma R.; Ordaz-Robles, Erick R.; González-Salazar, María del C.; Springall Del Villar, Rashidi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background Systemic arterial hypertension is linked to a heightened risk of cardiovascular diseases on a global scale. In Mexico, nearly half of adults in vulnerable conditions experience hypertension. Imbalance in the oral and intestinal microbiota composition has been observed in patients with hypertension, documented by a decrease of bacteria producing short-chain fatty acids, which play a critical role in blood pressure regulation. Aim To examine the cytokines’ profile and assess the characteristics of oral and gut microbiota in obesity-related hypertension in Mexican patients. Methods A cross-sectional, observational, and analytical study was carried out. Twenty-two patients were categorized by their body mass index (BMI) as overweight and obese, and the diagnosis of primary hypertension. DNA from supragingival dental plaque and feces samples was used to carry out 16S rRNA sequencing. Additionally, 13 cytokines were quantified. Results In the oral microbiota, Kluyvera was found to be significantly enriched in obese compared to overweight patients. Instead, the gut microbiota was dominated by Firmicutes. However, the correlation between certain genera and proinflammatory cytokines was noted. Conclusion This exploratory study provides insights into the complex relationship between the oral and gut microbiota and their association with systemic inflammation in obesity-related hypertension.